Assessing the Efficacy of Pedagogical Strategies in Enhancing English Language Proficiency - Lubis, Indri Harmaili (International Journal of English and Applied Linguistics (IJEAL), 2023)
English proficiency is crucial for students, especially in mandatory university programs. Effective teaching methods and pedagogical strategies significantly enhance English skills through active learning, problem-solving, and technology utilization. These strategies require pedagogical competence, including Information and Communication Technology (ICT) proficiency and quality instruction, and facilitate continuous assessment. Prior studies indicate positive correlations between pedagogical competence and language proficiency, subject performance, and numeracy skills. This research explores the impact of teaching and learning methods on students' English language proficiency and learning outcomes. Linear regression analyses reveal Teaching Aspect's positive influence on English Proficiency (coef: 0.1687, p-value: 8.82E-13), Enhancing Learning (coef: 0.1226, p-value: 5.18E-13), and Supporting Learning Process (coef: 0.04608, p-value: 0.00062). Learning Method significantly affects English Proficiency (coef: 0.5263, p-value: 1.92E-14), Enhancing Learning (coef: 0.3693, p-value: 1.66E-13), and Supporting Learning Process (coef: 0.15702, p-value: 7.05E-05). These findings underscore the positive relationships between these variables and their contributions to language proficiency and learning experiences, emphasizing the role of pedagogical competence in shaping educational outcomes